Fast Fashion: Theory and Evidence from Portuguese Textile and Clothing Firms - Ana P. Fernandes; Heiwai Tang (Center for Economic Studies and ifo Institute (CESifo), 2020)
We study how firms respond to import competition by increasing the speed of trade. We use data on all Portuguese textile and clothing exporters' monthly transactions and exploit the exogenous increase in competition following the removal of Multi-Fibre Arrangement (MFA) quotas on Chinese exports. The removal of quotas is associated with an increase in the price and frequency of export transactions and with a reduction in average distance of firms' exports. We rationalize our findings with a heterogeneous-firm model of exporting where firms decide which markets to serve as well as the frequency of transactions and the quality of exported products in each market. In response to low-wage competition, the more productive firms increase exports of high-quality products to nearby markets, while the less productive firms drop out from distant and low-income markets. These changes in export patterns imply that advanced economies become more specialized in "fast-fashion" —exporting higher quality products to closer markets at higher frequency.
Keywords: F10; F20; 330; export frequency; fast fashion; just-in-time trade; low-wage country competition; heterogeneous firms; quality upgrading